2021
DOI: 10.1123/jmld.2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Parent Perspectives and Motor Competence in Children With CHARGE Syndrome

Abstract: Children with CHARGE syndrome, an extremely complex, highly variable genetic disorder, are significantly delayed in the onset of their motor milestones in comparison with children without disabilities due to sensory and motor deficits as well as lengthy hospitalizations and reduced physical activity. Currently, the role of parents’ perceptions and participation in the motor development of their child with CHARGE is unknown. The purpose of this study was to examine the associations between parents’ perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…Articles were assessed for eligibility based on inclusion and exclusion criteria. For inclusion in Study 1, articles were required to incorporate all of the following: (a) human subjects and not solely a cellular, molecular, or animal model study; (b) a group of individuals with a confirmed diagnosis of ASD 4 (psychiatric comorbidities were permitted in the ASD group); (c) a NT control group, or data reported from an ASD group that could be compared to established population norms (i.e., standard scores from a norm-referenced measure of gross motor skills, age of gross motor milestone achievement); (d) a continuous measure of gross motor ability, defined as involving the action of large muscle groups (i.e., arms, legs, or torso), consistent with developmental theory, assessment, and research on motor development (Haibach-Beach et al, 2017); (e) at least 10 participants in both the ASD and NT groups, as very small studies would introduce more noise than signal into the data set and reduce power for detection of mean effect size (Hedges & Pigott, 2001) 5 ; (f) original empirical data; (g) full-text availability in English; (h) a participant sample that did not overlap with other included articles, in order to ensure that the assumption of independence between studies was upheld 6 ; and (i) data presented in a form that allowed for conversion to a SMD effect size (or the necessary data were able to be procured from the authors). Studies were excluded from Study 1 if they satisfied any of the following criteria: (a) an ASD group that consisted solely of participants with a genetic or neurological disorder known to affect motor function (e.g., Fragile X, Cerebral Palsy), as this would inflate effects; (b) only measures of fine motor skills, which was defined as precise movements of smaller muscles in the wrists, hands, or fingers (e.g., grasping, handwriting; Haibach-Beach et al, 2017); (c) only measures of atypical stereotyped movements or repetitive motor behaviors (as this meta-analysis did not aim to examine differences in motor behaviors that are included in the diagnostic criteria for ASD, which would be expected to differ between groups); (d) the article was solely a literature review or theoretical article.…”
Section: Methodsmentioning
confidence: 99%
“…Articles were assessed for eligibility based on inclusion and exclusion criteria. For inclusion in Study 1, articles were required to incorporate all of the following: (a) human subjects and not solely a cellular, molecular, or animal model study; (b) a group of individuals with a confirmed diagnosis of ASD 4 (psychiatric comorbidities were permitted in the ASD group); (c) a NT control group, or data reported from an ASD group that could be compared to established population norms (i.e., standard scores from a norm-referenced measure of gross motor skills, age of gross motor milestone achievement); (d) a continuous measure of gross motor ability, defined as involving the action of large muscle groups (i.e., arms, legs, or torso), consistent with developmental theory, assessment, and research on motor development (Haibach-Beach et al, 2017); (e) at least 10 participants in both the ASD and NT groups, as very small studies would introduce more noise than signal into the data set and reduce power for detection of mean effect size (Hedges & Pigott, 2001) 5 ; (f) original empirical data; (g) full-text availability in English; (h) a participant sample that did not overlap with other included articles, in order to ensure that the assumption of independence between studies was upheld 6 ; and (i) data presented in a form that allowed for conversion to a SMD effect size (or the necessary data were able to be procured from the authors). Studies were excluded from Study 1 if they satisfied any of the following criteria: (a) an ASD group that consisted solely of participants with a genetic or neurological disorder known to affect motor function (e.g., Fragile X, Cerebral Palsy), as this would inflate effects; (b) only measures of fine motor skills, which was defined as precise movements of smaller muscles in the wrists, hands, or fingers (e.g., grasping, handwriting; Haibach-Beach et al, 2017); (c) only measures of atypical stereotyped movements or repetitive motor behaviors (as this meta-analysis did not aim to examine differences in motor behaviors that are included in the diagnostic criteria for ASD, which would be expected to differ between groups); (d) the article was solely a literature review or theoretical article.…”
Section: Methodsmentioning
confidence: 99%
“… 61 , 64 , 65 Smaller performance improvements seen in the Dlg2 +/− mice in early trials might also be explained by changes including altered attention, motivation or physiological “warm up” effects that are more specifically associated with within‐session. 66 , 67 , 68 , 69 However, using a more prolonged motor learning protocol (7 trials/day for 3 days) to better observe learning and memory function, Dlg2 +/− mice similarly showed deficits in early within‐session learning. But they also showed a performance deficit that persisted across at least 3 days of training.…”
Section: Discussionmentioning
confidence: 99%
“…To appreciate the novelty and impact of Holt's account of physicality, it is relevant to begin by considering how physicality has often been discussed within the context of the cybersport thesis, namely in terms of motor skills (Hilvoorde and van Pot, 2016 ; Jenny et al, 2017 ; Rosell Llorens, 2017 ; Parry, 2019 ). To begin with, motor skills have been described as falling on a spectrum between fine and gross, a distinction spelled out by Haibach-Beach et al ( 2011 ) with reference to the nature of the physical movements and the width of muscle groups deployed. Fine motor skills can be understood as bodily movements that primarily involve control and accuracy, with a narrow range of muscle groups deployed, such as we might find in dart games.…”
Section: Physicality As Motor Skillsmentioning
confidence: 99%